Study on the importance of credit as financial leverage in agricultural development - Darium Stan (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 5th Edition of the International Symposium, November 2014, Bucharest, 2014)
Romanian agriculture is closely related to Romanian village life and is defined as the creatures and the whole of eternity. To think that there is little work to invest in land fertility, agricultural durability invest without having in mind that in Romania the whole eternity of mankind was born in the country. I forget a fundamental truth, proven time and space. Under state law defining Roman in all investments are taken into account the principle of Corpus en Animo where body is the earth that is more stable investment. The study examined a mistake exercised due modernism and of which we Romans have come to praise and idolism mess. It is said that we Romans did not have the capacity, nor the call to use and to modernize agricultural structures. At the beginning of the sixteenth century, Thomas More was a descriptive statement of England considering it as "country where sheep outnumber people." Somewhere in England in 1901 when industrial explosion occur only 9% of the farming population has chosen to respond to migration of rural population to urban areas. It is true that later happened industrial expansion and depopulation of villages in England, but the agricultural sector did not happen to be neglected and fall in disuse time. Structural changes in the agricultural sector have been made with specific consequences, but the same sector at a time proved to be a key ally of England leading the way to becoming the most powerful industrial countries. Romanian agriculture required to adapt perpetual metamorphoses upgrades, misuse, dismantling disuse and writing his own history as the volume and whole chapters.
Keywords: 330; Romanian agriculture; investments; Roman law; principle